WAYS TO REDUCE INCOME DISPARITIES BETWEEN URBAN AND RURAL AREAS (International journal of artificial intelligence, 2026)
This article analyzes the main causes of income disparities between urban and rural areas and explores ways to reduce them. The study examines the impact of employment levels, infrastructure development, quality of education, entrepreneurial activity, and access to financial services on income formation. In addition, the importance of diversifying economic activities in rural areas, developing small businesses, and state support mechanisms is substantiated.